Antihyperglycaemic activities of xanthone rich extract of mangosteen (garcinia mangostana) - Tengku Muhamad Faris Syafiq bin Tengku Zakaria (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2015)
Mangosteen (Garcinia mangostana Linn.) fruit pericarp has been used for centuries as a folk medicine. The study was conducted to evaluate the in vitro and in vivo antihyperglycaemic potential of G. mangostana extract (GME). The α-mangostin content in the extract was measured using HPLC and investigated for total phenolic and flavonoid contents. Antioxidant activities were measured by DPPH radical scavenging and reducing power assays whereas in vitro antidiabetic activities were evaluated by inhibition of α-glucosidase and α-amylase enzymes. Effects of GME on adipocyte cells were assessed through MTT assay, adipogenesis and glucose uptake measurements. In animal study, oral administration of GME1 (50 mg/kg), GME2 (100 mg/kg) and GME3 (200 mg/kg) to STZ-induced diabetic rats in single-dose (acute) and multiple-dose study (sub-acute) were examined. Serum biochemical parameters and histopathological alterations were evaluated and compared to standard hypoglycaemic drug, glibenclamide. The results showed that total phenolic and total flavonoid contents were 122.2±1.04 mg GAE/g and 72.8±1.75 mg QE/g of dry extract, respectively. DPPH radical scavenging activity and reducing power capacity reported with EC50 of 48.2 μg/ml and IC50 of 98.2 μg/ml, respectively. The enzymatic inhibition of α-glucosidase and α-amylase revealed higher percentage of inhibition comparable to acarbose with IC50 of 0.41 and 0.24 mg/ml, respectively. In cellular study, cytotoxicity assay reported that dose of less than 12.5 μg/ml does not affect cell viability. The differentiations of adipocytes were increased with higher GME concentration at 2.5 μg/ml, 5.0 μg/ml and 10.0 μg/ml. Glucose uptake measurements revealed a higher uptake of 2-deoxyglucose in GME2-treated cell (2243.3±232.3 cpm) as compared to GME1 (1864.0±146.3 cpm) and GME3 (1246.0±155.8 cpm). Oral administration of GME on diabetic rats indicated safe usage with absence of behavioural alterations, autonomic, neurological and toxic effects up to 2000 mg/kg. The results showed a significant reduction of glucose level in GME2 and GME3 (p<0.001) as compared to GME1. Total cholesterol, serum triglyceride, urea and creatinine were reduced in the treatment group while total protein contents were increased. Histological assessment of livers and kidneys revealed reduced lesions whereas mild regenerative activity of β-cell was observed in pancreas of diabetic rats. In conclusion, the findings demonstrated that GME could be a potential source in diabetes management owing to its antioxidant content, delayed carbohydrate digestion, induction of adipocyte differentiation, improvement in glucose uptake and antihyperglycaemic effect in diabetic rats.